Comparison of Data Inquiry and Cost Structure Methods to Arrange Owner Estimate (Case Study of Carbon Steel Pipe Procurement at PT XYZ) - Amarilies, Harummi; Erwitie, Gitiza; Sari, Alifiana Permata (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
In material sourcing, one of the procurement processes that should be completed before evaluating and selecting the vendor is making an Owner Estimate (OE). The most common way to arrange an OE is by making Data Inquiry, where the arranger asks for a certain product’s price from a list of providers or vendors. However, this method does not describe in detail how the price of the product is constructed, so the company, which is doing the procurement process, tends to set a higher OE. To reduce this risk, another method to determine OE is introduced. This method applies a Cost Structure method to calculate production and transportation costs, the expenses a vendor should cover when manufacturing the products. Using a total of 20 scenarios that varied the percentage of profits, the increase in carbon steel plate costs, and the overhead costs, using Cost Structure Method can lower the Owner Estimate between 0.51% to 24.46%. The last scenario with 20% increase in profit, 20% increase in carbon steel plate cost and 20% increase in the overhead cost resulted to -2.55% reduce of Owner Estimate. This new method is proven effective as an alternative way to arrange OE for similar material.